Penerapan Metode Lean Project Management Dalam Perencanaan Proyek Smart Shopping Scanner Di PT. ABC - Fitriatus Sholeha; Sumiati Sumiati (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
In this era, technology is developing very rapidly in various sectors ranging from industry, health, education, retail, and various other sectors. The development of technology is linear with human needs that must be met quickly, easily, and practically. A sector that can fulfill human needs is the trade sector. Currently, the trade sector is one of the sectors that is highly developed along with the trend of online shopping. Although online shopping is currently very popular, it does not mean that offline shopping is necessarily abandoned. Conventional payment systems usually require customers to queue at the cashier to make payments after choosing grocery items. Therefore, there is a need for technological innovation that can overcome this. The solution to overcome these problems is by planning to create a Smart Shopping Scanner machine by considering lean project management. Based on the results of the research that has been done, the application of the Lean Project Management method to the Smart Shopping Scanner project planning at PT ABC has resulted in significant improvements. Reduction of project completion time by 33.33%, reduction of component inventory value by 40%, and improvement of team communication by 66.67% show the effectiveness of this method in overcoming waste and increasing efficiency.